Relevance of In-house Publications in Knowledge Management: A Case Study from Naval Physical and Oceanographic Laboratory - K.P.B., Moosad; M.M., Letha; S., Anantha Narayanan (DESIDOC Journal of Library & Information Technology, 2016)
Several aspects of knowledge management in R&D institutions have been studied and reported by researchers in the past. However, studies on the relevance of in-house publications have not been reported so far. In-house publications have a significant role to play in effective knowledge management, especially in large R&D institutions. Such institutions generally have a compartmentalised structure, wherein each compartment delves deeper and deeper into areas of their own interest and expertise. As the depth and detail of the subject under study increases communication between the compartments becomes weaker. Dialogues within the compartments become jargon-ridden and incomprehensible to those belonging to the other compartments. In organisations with thousands of employees, distributed in several branches, situated in geographically distributed locations, communication of the knowledge generated at one place to another pose lots of problems. In-house publications are one of instruments that seek to correct this situation to a significant extent. To communicate the right information to the right people needs careful handling of the subject at corporate level. Subsequently, the number of in-house publications may become quite large. This article presents the case of Naval Physical and Oceanographic Laboratory at Kochi, India, which resorts to several in-house publications for effective knowledge management within the organisation.